(untitled) (Acta Scientiarum. Biological Sciences, 2010)
The effect of the variables pantothenic acid, yeast extract and sodium chloride, as well as the cell permeabilization technique, were investigated on the formation of levan, ethanol, sorbitol and biomass of Zymomonas mobilis, using a 24-1 fraction factorial design. Cell growth was determined by turbidimetry at 605 nm, relating it to a biomass with a dry weight calibration curve. Reducing sugars were quantified according to Somogyi and Nelson. Total sugars were quantified by the phenol-sulfuric acid method, sorbitol by HPLC and ethanol. The levan produced was precipitated by the addition of absolute ethanol and quantified in fructose units. In levan biosynthesis, the variable that had the largest contribution was cell condition. The results suggested that the factors that most affected biomass and ethanol formation were sodium chloride concentration and cell condition that affected negatively on production. For sorbitol, the variable that had a significant effect was permeabilization, which decreased its synthesis. Studies to amplify the range of established factors would be important.